Evaluation of the readiness of Genipa americana for in vitro gas production - Herrera-Pérez, Jerónimo; Sanchez Santillan, Paulino; Lorenzo-Rojas , Álvaro; Almaraz-Buendía, Isaac; Bottini-Luzardo , Maria (Ecosistemas y Recursos Agropecuarios, 2025)
The protocols of the in vitro gas production technique are intended to be standardized when evaluating tree species for feeding ruminants. The objective was to determine the effect of sample arrangement in the biodigester, as well as to characterize in vitro mature and immature leaves and fruits of Genipa americana. In a vial, the sample was placed directly or in a poly-silk bag; 40 mL of anaerobic culture medium, under CO2 flow and 10 mL of fresh rumen fluid as inoculum. The vials were incubated 72 h at 39 °C. Biogas production was measured at 2, 4, 6, 8, 10, 10, 12, 24, 48, and 72 h and dry matter degradation (DMD) at 72 h. The statistical analysis was a completely randomized design with a 3 x 2 factorial arrangement, with type of sample (leaf, immature and mature fruit) and disposition (direct or bagged) as factors. Biogas production showed no interaction between factors (P > 0.05); but DMD showed interaction (P ≤ 0.05). Biogas production showed no interaction between factors (P > 0.05); but DMD showed interaction (P ≤ 0.05). Biogas production did not show differences in sample arrangement (P > 0.05), except for 2 h (P ≤ 0.05). Leaves presented lower cumulative biogas production (P ≤ 0.05). DMD was different in the arrangement of mature and immature fruits (P ≤ 0.05), while in leaves there were no differences by arrangement (P ≤ 0.05). Sample arrangement affected the values of DMD and biogas production at 2 h in fruits.